Phase change materials and carbon nanostructures for thermal energy storage: a literature review - Amaral, C. (2021)
The high thermal conductivity of carbon based nanostructures (CNs) has been recognized appropriate to be integrated into phase change materials (PCMs) to enhance the overall thermal properties of the obtained nanocomposites. The equilibrium of the possibility to enhance the thermal conductivity of the PCMs and the latent heat capcity are the key for their ability to store or dissipate a large amount of energy in a short period of time. This paper gives an update overview summarizing the state-of-the-art concerning nanocomposites prepared using PCMs and CNs with emphasis on the improvement of the latent heat capacity and of the thermal conductivity. Focus is directed towards experimental research studies regarding the enhancement of the thermal properties (thermal conductivity and the latent heat capacity) of PCMs obtained by the addition of the CNs by means of the encapsulation method. The majority of the reported research studies focus mainly on the thermal characterization of PCMs nanocomposites, however there is scarce information about the mechanisms explaining why/how the thermal properties are enhanced. This review outlines the results of the thermal conductivity and the latent heat capacity of PCMs/CNs nanocomposites, trying to identify the features that lead to the improvement of their thermal properties.